Natur und Kunst bei Claudian Poetische ›concordia discors‹ - Nierste, Wiebke (Millennium-Studien / Millennium Studies, 2022)
This volume focuses on twelve of the so-called Carmina minora by the late ancient poet Claudius Claudianus (ca. 370-404 CE), which describe of different kinds. Nature, art, and the concordia discors that characterises both play a special role in the textual analyses. Together with distinctive intra- and intertextual references, they are understood as key aspects of Claudian's poetics.